Impact of the COVID-19 Pandemic on Psychosocial Distress in Adolescents with Obesity Compared to Those with Type 1 Diabetes: Results from the KICK-COVID Study in Germany - Susann Weihrauch-Blüher; Susanna Wiegand; Sascha Tittel; Susanne Greber-Platzer; Stefanie Lanzinger; Clemens Kamrath; Kirsten Minden; Claudia Sengler; Sabine Linke; Antje Büssenschütt; Felix Reschke; Julia Göldel; et al. (Obesity Facts)
Introduction: The aim of this study was to investigate the impact of the COVID-19 pandemic on psychosocial well-being in adolescents with obesity compared to those with type 1 diabetes. Methods: As part of the German KICK-COVID Study, adolescents aged 12–21 with overweight or obesity from the German/Austrian Adiposity Follow-up Registry (APV) completed well-being, anxiety, and depression questionnaires (WHO-5, GAD-7, PHQ-9) during routine visits amidst the COVID-19 pandemic. By multivariable linear regression models, adjusted for age, gender, and immigration background, the association between psychosocial distress, anthropometrics, and cardiometabolic risk factors was analyzed. Data were compared to those of youth with type 1 diabetes from the German/Austrian Diabetes Follow-up Registry (DPV) and normative values from the general population. Additionally, a mediation analysis examined the impact of loneliness on mental health through media consumption. Results: From June 2021 to September 2023, 235 adolescents from 6 German and 1 Austrian pediatric obesity centers were enrolled. Results were compared to 235 age- and gender-matched participants from the DPV registry (54.04% males; mean age 15.21 ± 1.66 years) and normative values. Youth with type 1 diabetes were more anxious about their health risk, but distress factors were more pronounced in the APV group (p < 0.001). Girls from the APV group showed higher mental distress than boys across all applied questionnaires, but not for age, BMI-SDS, and migration background as predictors. Perception of loneliness correlated with poorer mental health outcomes, but it was not associated to media consumption. Comparisons with normative values revealed significantly higher depression and anxiety scores (p < 0.001) and lower well-being scores in the APV group (p < 0.01). Conclusions: Youth with obesity and diabetes experienced significant psychosocial distress during the COVID-19 pandemic. Disease-specific differences were observed on the level of single items: Adolescents with type 1 diabetes expressed heightened concern about their health risks, while those with obesity reported lower self-esteem, increased suicidal thoughts, and fluctuating appetite. Female gender appeared to pose an additional risk factor. Media consumption was notably higher in the APV cohort. Healthcare providers should be vigilant regarding psychological comorbidities in youth with chronic conditions, particularly during periods of heightened stress.